2017
DOI: 10.2749/101686617x14881932436212
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Robustness in the Design of Steel and Composite Frame Structures

Abstract: The topic of progressive collapse of structures has increasingly received particular consideration over recent years, with numerous studies of various forms having been seeking to explore the complex mechanics of the problem and define ways of minimising its effects. Through a continuing research program at Imperial College London, considerable advance has been made in understanding the physical features of the progressive collapse response of frame structures, identifying the role of the several different con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…The flexural action effect increases as the beam span decreases and/or the bending moment capacities of the beam-column connections increase. The previous studies also demonstrated how different collapse resistance mechanisms are affected by various structural parameters [64,65]:…”
Section: Mechanics Of Structural Behaviormentioning
confidence: 91%
See 2 more Smart Citations
“…The flexural action effect increases as the beam span decreases and/or the bending moment capacities of the beam-column connections increase. The previous studies also demonstrated how different collapse resistance mechanisms are affected by various structural parameters [64,65]:…”
Section: Mechanics Of Structural Behaviormentioning
confidence: 91%
“…This configuration is probably more appropriate for studying the behavior of the midspan joint rather than the response of the complete double-span beam system. The previous studies also demonstrated how different collapse resistance mechanisms are affected by various structural parameters [64,65]:…”
Section: Common Configurations Of Test Specimensmentioning
confidence: 91%
See 1 more Smart Citation
“…Among them the need for improved modelling and design guidance were highlighted and also the necessity of detailed test data. In a review paper, Stylianidis and Nethercot [3] suggest that the development of suitable prediction methods for post-limit stiffness and deformation capacity characteristics should be the aim of future research studies.…”
Section: Introductionmentioning
confidence: 99%
“…In structural engineering, it relates to the assessment or investigation of structural or material properties or their verification with theoretical calculations. The initial structural testing can be referred to the earliest stages of development of mechanics and experimentation with the literature referring to tests by Galileo and Newton on plane motion and forces, Hooke on elastic properties [1][2][3][4]. However with the availability of several testing facilities alongside the new concepts and methods of structural analysis and design, experiments have played very crucial roles in the development of structural engineering particularly over the last half a century.…”
Section: Introductionmentioning
confidence: 99%